Effects of aerobic training on the lactate response during a 30-min time trial and a VO2max test in road cyclists - Martin, D. T.; Andersen, M. B.; Lee, H. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
The purpose of this study was to measure performance and physiological indicators of exercise intensity during a graded exercise test (GXT) and a 30-min time trial (30TT) in road cyclists before and after aerobic training. Six Australian National Squad male road cyclists (MEAN± SD; 23.5± 1.5 yrs, 179.8± 3.1 cm, 69.5± 5.6 kg, 5.02± .41 L.min-1 O2 peak, 412.5± 28.2 W PPO), performed two GXTs and two maximal 30TTs before and after 2 months of early season training (3200-4800 km). Testing was performed on a magnetically braked cycle ergometer (Lode) and all cyclists had previously completed testing protocols. The GXT began at 100 W and increased 50 W every 5 min until exhaustion. For the 30TT cyclists produced the highest power output possible for 30-min. Every 5 min during both tests heart rate (HR), rating of perceived exertion (RPE), and blood lactate (HLA), pH, and bicarbonate (HCO3-) were measured. Threshold power output was determined during the GXT using the DMAX technique. Dependent variables were analysed using a series of paired t-tests. Significance was accepted when P<.10. Training was associated with the following changes during the GXT: increase in PPO (380± 40 to 413± 28 W, P<.10), increase in DMAX power (296± 42 to 327± 26 W, P<.10), decrease in DMAX lactate (4.1± 0.9 to 3.0+0.5 mM, P<.10) with no change in DMAX HR, DMAX O2, or O2peak. As expected, training improved the 30TT power (326± 27 to 350± 19 W, P<.10) but did not change 30TT HR (186± 5 to 183± 6 bpm, NS) or 30TT RPE (16.7± 0.9 to 17.0± 1.0 RPE units, NS). Surprisingly, the 30TT HLA increased (6.7± 1.6 to 8.2± 1.4 mM, P<.10), pH decreased (7.353± .019 to 7.307± .037 pH units, P<.10) and HCO3- decreased (18.5± 2.0 to 15.4± 1.5 mM, P<.10). In summary, male cyclists generally complete a maximal 30TT ~25 W above DMAX power, ~2-4 mM above DMAX HLA, and ~10-15 bpm above DMAX HR. Training improved DMAX power and 30TT power by 7-10%. Although 30TT HR and RPE were not influenced by training, 30TT HLA was higher (~1-2 mM) and pH and HCO3- were lower. Thus, training induced improvements in the HLA - Power curve (DMAX) appear to predict improvements in 30TT power but not 30TT HLA or pH, highlighting a difference between GXT and 30TT testing.